Development of Interactive Learning Media through Chat Bots on Reproduction Material in Elementary Schools - Kusyuliarto, K; Murtiyasa, Budi; Desstya, Anatri; Rahmawati, Laili Etika (Universitas Muhammadiyah Surakarta, 2024)
Purpose: The purpose of this study was to describe the conceptual understanding ability of elementary school students in Surakarta in learning Natural and Social Sciences (IPAS) through the Chat Bot application. The type of research in this article is development through the ADDIE model. Methodology: The type of research in this article is development through the ADDIE model. The subjects of this study were grade VI teachers, principals, and 114 grade VI students of Sampangan, Wiro Paten, and Kedung Lumbu State Elementary Schools, Pasar Kliwon District, Surakarta City. The data obtained related to the Chat Bot application were declared valid by two validators. Data collection techniques consisted of questionnaires and interviews, for data analysis through interview results, observation results, percentages and average scores. Results: The results of this study showed an average based on five indicators that were very good. The indicator interpreted with an average of 2.43 good categories. The indicator gave examples with an average of 2.69 very good categories. The indicator was classified with an average of 2.90 very good categories. The indicator drew conclusions with an average of 2.72 very good categories. The indicator explains with an average of 2.86 very good categories. The average of the five indicators is 2.72 very good categories. Applications/Originality/Value: The Chat Bot application in learning science reproduction in Elementary Schools in Surakarta is considered effective because it is able to improve the understanding of abstract concepts to be more real and easy to understand.